Mechanical Properties of Untreated and Alkaline Treated Kenaf and Ramie Fabric Reinforced Epoxy Composites - Md Rezali, Khairul Azmi (2008)
This research work is concerned with the determination of tensile, flexural and impact properties of kenaf and ramie fabric reinforced epoxy composites at three and eleven layers of fibre and different treatment (i.e. alkaline or non-alkaline) methods. The specimens were prepared using hand lay-up technique. The tensile and flexural tests were performed using an INSTRON 5507 universal testing machine and the high velocity impact test were performed using Ballistic Automated Network Gun systems (BANG) at projectile speed of 73 m/s, 160 m/s, 230 m/s and 278 m/s. In this study, the fibre has been treated by 6% alkaline treatment. Two main purposes of this thesis are to determine and compare the result of tensile, flexural and impact properties for kenaf and ramie composite, and also for composite (kenaf and ramie) with and without 6% of alkaline treatment. The result shows that 6% of alkaline treated of composites possess decreased value of tensile and flexural strength for kenaf and ramie composite because of high percentage of alkaline treatment. However, the increased value of impact properties found after adding 6% of alkaline treated. The outcome of the result clearly shows that ramie composite is better than kenaf composite in tensile and flexural properties. But in impact properties, the outcome result shows that kenaf composite is better than ramie composite